Efektivitas "Jogja Smart Service" Terhadap Pelayanan Publik di Kota Yogyakarta - Alfi Novriando; Eko Priyo Purnomo; Lubna Salsabila (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2020)
This study aims to determine the effectiveness of "Jogja Smart Service" on Public Services in the City of Yogyakarta. This research-based on the study of the effectiveness of a Smart City product that is to realize Public Smart Service in an urban setting. This research is a descriptive qualitative study with literature review techniques and data analysis sources obtained from documents in the Jogja Smart Service application. Public services in the city of Yogyakarta have been integrated into one Jogja Smart Service application service so that it can be used by the people of Yogyakarta City effective and efficiently.